2012
DOI: 10.1089/scd.2011.0139
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose-Derived Stem Cells Impair Natural Killer Cell Function and Exhibit Low Susceptibility to Natural Killer-Mediated Lysis

Abstract: Human adipose-derived stem cells (hASCs) have been successfully used in treating numerous diseases. However, several aspects need to be considered, particularly in the context of allogeneic cell therapy. To better understand hASCs-host interactions, we studied the phenotype of hASCs and their modulatory effect on natural killer (NK) cells by using bone marrow-mesenchymal stem cells (hBM-MSCs) as a reference. The hASCs displayed a lower susceptibility to NK cell-mediated lysis and a lower expression of ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 56 publications
5
83
1
3
Order By: Relevance
“…MSCs are considered a promising tool for cell therapy, in particular for inflammatory diseases, based on their immunomodulatory properties and paracrine effects through trophic factors with anti-fibrotic, anti-apoptotic or pro-angiogenic properties [29,30] . MSCs regulate the function of a broad range of immune cells [30][31][32][33][34][35][36][37] , and are activated by inflammatory mediators released from activated immune cells (i.e., IFNγ, IL1β and TNFα) [38,39] . The mechanisms involved in the immunoregulatory activity of MSCs are still under investigation but rely on both cell contact-dependent mechanisms (i.e., Jagged1-Notch1 interaction, Fas-Fas-L interaction) [40,41] and paracrine effects through the release of soluble factors including hepatocyte growth factor, prostaglandin-E2 (PGE2), TGF-β1, nitric oxide (NO), IL-10, IL-6, heme oxygenase-1 (HO-1), HLA-G5 or the enzymatic activity of indoleamine 2,3-dioxygenase [42] .…”
Section: Mscmentioning
confidence: 99%
“…MSCs are considered a promising tool for cell therapy, in particular for inflammatory diseases, based on their immunomodulatory properties and paracrine effects through trophic factors with anti-fibrotic, anti-apoptotic or pro-angiogenic properties [29,30] . MSCs regulate the function of a broad range of immune cells [30][31][32][33][34][35][36][37] , and are activated by inflammatory mediators released from activated immune cells (i.e., IFNγ, IL1β and TNFα) [38,39] . The mechanisms involved in the immunoregulatory activity of MSCs are still under investigation but rely on both cell contact-dependent mechanisms (i.e., Jagged1-Notch1 interaction, Fas-Fas-L interaction) [40,41] and paracrine effects through the release of soluble factors including hepatocyte growth factor, prostaglandin-E2 (PGE2), TGF-β1, nitric oxide (NO), IL-10, IL-6, heme oxygenase-1 (HO-1), HLA-G5 or the enzymatic activity of indoleamine 2,3-dioxygenase [42] .…”
Section: Mscmentioning
confidence: 99%
“…MSCs have been known to suppress activity of NK cells with regards to IFN-γ secretion and proliferation [51,71,72]. ASCs, specifically, are capable of such suppression [73] and are themselves poorly susceptible to lysis by NK cells [74].…”
Section: Effects On B Lymphocytesmentioning
confidence: 99%
“…ASC activation or suppression of one or more specific Tcell subsets may significantly affect the observed overall growth inhibition or stimulation of T cells [5][6][7]9,[12][13][14][15][16][17]. Several studies have demonstrated that ASCs inhibit cells of both the innate and adaptive immune response through secretion of soluble factors such as prostaglandin E 2 , TGF-b1, hepatocyte growth factor, and production of factors that include inducible nitric oxide synthase and indoleamine 2,3-dioxygenase [7,9,12,13,[20][21][22].…”
Section: Cd4mentioning
confidence: 99%
“…Several studies have demonstrated that ASCs inhibit cells of both the innate and adaptive immune response through secretion of soluble factors such as prostaglandin E 2 , TGF-b1, hepatocyte growth factor, and production of factors that include inducible nitric oxide synthase and indoleamine 2,3-dioxygenase [7,9,12,13,[20][21][22]. Another potential mechanism of immune interference involves ASC-mediated induction of iT regs from naive CD4 + T cells by direct contact.…”
Section: Cd4mentioning
confidence: 99%
See 1 more Smart Citation